2010
DOI: 10.1021/pr100727m
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Approach for Investigation of Effects of Dengue Virus Infection Using the EA.hy926 Cell Line

Abstract: This paper describes a multiplatform analytical approach combining proton nuclear magnetic resonance ((1)H NMR) spectroscopy and mass spectrometry (MS), together with pattern recognition tools in a metabolomic study used to investigate the effects of dengue virus infection. The four serotypes of dengue, DEN-1, DEN-2, DEN-3, and DEN-4, were inoculated into the EA.hy926 cell line, which was then incubated for various time intervals. Principal component analysis (PCA) of the (1)H NMR and MS data revealed metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
59
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 25 publications
2
59
1
Order By: Relevance
“…Corroborating this result, the sPLS-DA statistics showed a significant increase in plasma tyrosine concentrations in DHFp and DHFs patients from the onset of symptoms to the defervescence phase of the disease (Table 3). Although our analysis did not indicate that phenylalanine is a potential metabolite marker, an increase in the plasma phenylalanine concentrations (22) and in intracellular tyrosine concentrations (18) have been reported in DENV infection.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Corroborating this result, the sPLS-DA statistics showed a significant increase in plasma tyrosine concentrations in DHFp and DHFs patients from the onset of symptoms to the defervescence phase of the disease (Table 3). Although our analysis did not indicate that phenylalanine is a potential metabolite marker, an increase in the plasma phenylalanine concentrations (22) and in intracellular tyrosine concentrations (18) have been reported in DENV infection.…”
Section: Discussioncontrasting
confidence: 83%
“…Since the metabolic resources crucial for viral replication are provided by host cells, the detection of changes in the metabolic profile associated with the pathological condition could help with the identification of markers of prognostic and diagnostic importance as well as the development of specific treatment strategies. In this sense, it has been demonstrated that infection of endothelial cells with the four DENV serotypes provoked significant alterations in the levels of extracellular metabolites, including amino acids and tricarboxylic acid (TCA) cycle intermediates (18). Different responses to the four serotypes were observed, which could be related to the broad range of manifestations and different DENV infection outcomes observed in the clinical setting.…”
mentioning
confidence: 99%
“…Previously, a multiplatform approach was developed to measure the levels of a limited number of extracellular metabolites following DENV infection of the human endothelial hybrid cell line EA.hy926 (21). However, a comprehensive examination of host cellular metabolism during DENV infection of primary human cells has yet to be conducted.…”
mentioning
confidence: 99%
“…HCMV was shown to induce multiple metabolic alterations, including upregulation of the tricarboxylic acid (TCA) cycle, fatty acid synthesis, pyrimidine nucleotide biosynthesis, and glycolysis. The metabolic effects of virus infection on human cells have now been investigated for several other viruses, including Kaposi's sarcoma-associated herpesvirus (KSHV), herpes simplex virus 1 (HSV-1), hepatitis C virus (HCV), human immunodeficiency virus (HIV), and dengue virus (1,(3)(4)(5)(6)(7). These studies have identified numerous metabolic perturbations induced by virus infection.…”
mentioning
confidence: 99%